Symbiont microcosm in an ant society and the diversity of interspecific interactions - Hashim, Rosli; Foitzik, S.; Witte, V.; Leingartner, A.; Sabass, L. (2008)
Colonies of the ponerine army ant Leptogenys distinguenda are regularly inhabited by a highly diverse symbiont fauna including insects, spiders, mites, crustaceans and even molluscs. Each of these myrmecophiles has adapted in a highly specific way to the lifestyle of its host. We studied this diverse myrmecophile fauna of L. distinguenda as a new model for multispecies parasitism to gain a better understanding of fundamental coevolutionary processes. Our study focused on behavioural and on chemical integration and exploitation strategies of the different symbiont species. In addition, we examined potential counterstrategies of the host ant. Myrmecophiles were studied both in large free-living L. distinguenda colonies and in more detail in parts of colonies separated for observation. We found that at least five myrmecophile species imposed cost on their host by exploiting its resources. Their impact varied considerably depending on both the type of resources exploited and their abundance. Myrmecophile species were well integrated into host societies either by chemical mimicry of host cuticular hydrocarbons or by remaining chemically insignificant, lacking most characteristic recognition cues. Despite these chemical integration strategies, host ants were able to recognize and kill the alien intruders to various degrees. This important finding demonstrates that symbiont populations are actively counter-regulated by the host. By constructing a host-parasite interaction network, we finally suggest that host defences can maintain myrmecophile diversity by keeping parasite populations small. This reduces interguild competition, comparable to top-down effects of predators on lower trophic levels in ecological food webs. (C) 2008 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.